2019
DOI: 10.3389/fmicb.2019.01876
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Proteomic Characterizations of Sfin-1, a Novel Lytic Phage Infecting Multidrug-Resistant Shigella spp. and Escherichia coli C

Abstract: Shigellosis is a public health threat in developed as well as developing countries like “India.” While antibiotic therapy is the mainstay of treatment for shigellosis, current emergence of multidrug-resistant strains of Shigella spp. has posed the problem more challenging. Lytic bacteriophages which destroy antibiotic resistant Shigella spp. have great potential in this context and hence their identification and detailed characterization is necessary. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 68 publications
3
17
1
Order By: Relevance
“…Accordingly, the maximum number of progenies released from one host bacterium was recorded as 151 PFU bacterial cell −1 . Although the latent period was fairly similar to the one observed for vB_SflS-ISF001 (20 min) 30 , but was markedly higher or lower than that recorded for pSf-2 (30 min) 56 , SH6 phage (16 min) 55 and Sfin-1 (15 min for S. dysenteriae and 10 min for S. sonnei ) 29 . Interestingly, the burst size of 2019SD1 was greater than that of other reported Shigella phages of Drexlerviridae family like pSf-2 (16 PFU infected cell −1 ) 56 , SH6 phage (103 ± 16 PFU infected cell −1 ) 55 and SsoS-ISF002 (76 ± 9 PFU infected cell −1 ) 27 .…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Accordingly, the maximum number of progenies released from one host bacterium was recorded as 151 PFU bacterial cell −1 . Although the latent period was fairly similar to the one observed for vB_SflS-ISF001 (20 min) 30 , but was markedly higher or lower than that recorded for pSf-2 (30 min) 56 , SH6 phage (16 min) 55 and Sfin-1 (15 min for S. dysenteriae and 10 min for S. sonnei ) 29 . Interestingly, the burst size of 2019SD1 was greater than that of other reported Shigella phages of Drexlerviridae family like pSf-2 (16 PFU infected cell −1 ) 56 , SH6 phage (103 ± 16 PFU infected cell −1 ) 55 and SsoS-ISF002 (76 ± 9 PFU infected cell −1 ) 27 .…”
Section: Resultssupporting
confidence: 65%
“…1 A). The plaque size was nearly similar to that observed for other Shigella phages namely vB_SsoS_008 (2.5–2.7 mm) 52 , but markedly higher or lower than that recorded for pSf-1 (4.5 mm) 53 , JK16 (4 mm) 28 , vB-SdyS-ISF003 (3 mm) 50 SsoS-ISF002 (0.5 to 3.0 mm) 27 , SH6 (2 mm) 54 , Sfin-1(1.5–2.0 mm) 29 , vB_SflS-ISF001 (0.5–2.0 mm) 30 . Analysis of TEM images of phage particles suggested that the 2019SD1 had an icosahedral capsid (60 ± 5 nm dia) and a 140 ± 6 nm long tail (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The isolated N. gonorrhoeae [ 36 ] lysogenic phage is from an activated prophage within its genome, while S. agalactiae [ 59 , 61 , 62 , 113 ] phages have been isolated environmentally. Shigella flexneri and S. sonnei have virulent phages [ 102 , 103 , 104 , 105 , 106 ], some of which are being used clinically to treat shigellosis [ 25 , 98 ]. However, these treatments have not been considered for use in the treatment of STIs, as historically, shigellosis is obtained through the traditional fecal–oral route.…”
Section: Challenges Associated With Application Of Phage Therapy In Bacterial Sexually Transmitted Infectionsmentioning
confidence: 99%
“…When compared with some other B. cereus phages [66][67][68], the burst size of DLc1 is relatively low and the latent period is shorter (Figure 8B). Although it has been shown that a large burst size is preferred in phage therapy [69], DLc1 with a short latent period and high adsorption efficacy also displayed its advantages.…”
Section: The Application Potentialmentioning
confidence: 99%